Tantangan dan Peluang dalam Penegakan Hukum Hak Pendidikan Bagi Penyandang Disabilitas - abdul jamal, Vivi Safaatul Janah P. Giana; Abdul Jamal, Zahra Ramadhani; Nurhayati, Siti (JPI (Jurnal Pendidikan Inklusi), 2024)
Law enforcement in inclusive schools includes implementing regulations that support inclusive education. These regulations are intended to ensure that all students, including those with special needs, have access to quality education that meets their needs. An example of a related regulation is Minister of National Education Regulation Number 70 of 2009 which states that inclusive education is an education delivery system that provides opportunities for all students to take part in education or study in an education with students in general. The aim of this research is to analyze and describe the government's efforts to advance inclusive education, as well as analyze and describe the programs implemented in inclusive education. So, in this material you will get a comprehensive understanding and quantitative methods, especially looking for factual data and validating it by researchers. The motivation for this research is to cite articles and reviews. Inclusive education is very necessary for people with disabilities and special needs. This is why people with disabilities and special needs have the same rights to education as normal people. Children with disabilities have the right to receive support from the education system, health services, employment providers and wider social services. Persons with disabilities have the same rights and must have the same responsibilities. The government and education ministry need to focus more on inclusive education by providing more interventions and support. Apart from that, these recommendations also highlight the importance of continuous evaluation of the implementation of inclusive education to ensure that inclusive education goals can be achieved.